Developmental signaling genes in ameloblastoma (2015)
Context: This study investigated the presence or absence of β-catenin and Patched1 (PTCH1) genes involved in the developmental pathway in ameloblastoma, in order to clarify the genetic etiology of this tumor. Aim: The aim of this study was to investigate whether PTCH1 and β-catenin genes are involved in the development of ameloblastoma. Subjects and Methods: Archived formalin-fixed paraffin-embedded specimens of 89 ameloblastoma cases from the year 2000 to 2010 were genotyped by polymerase chain reaction (PCR). Results: A total of 21 (23.6%) of the 89 ameloblastoma cases were positive for β-catenin gene, where 14/21 (66.7%) cases were mandibular ameloblastoma. Plexiform 5/21 (23.8%) and cystic 5/21 (23.8%) ameloblastoma were the most regular histological type positive for β-catenin. However, β-catenin positive was more in the feminine gender (11/19, 57.9%) than the masculine (8/19, 42.1%). Only one case was positive for PTCH1 gene and this was histologically a mandibular site and plexiform-type ameloblastoma. Conclusions: This study suggested that β-catenin and PTCH1 genes may play an important role in the pathogenesis of ameloblastoma.